Perkembangan Gamelan Jawa di Nusantara - Kholidah, Nur Diana (Maliki Interdisciplinary Journal, 2023)
This study aims to examine the development of Javanese gamelan as an Islamic cultural heritage in Indonesia. Javanese Gamelan is a traditional musical ensemble that has an important role in the cultural life of the Javanese people. In this context, this research focuses on the role and influence of Islam in the development and transformation of Javanese gamelan. The research method used is historical research and musical analysis. Historical research involves studying documents, literature, and archives related to the role of Javanese gamelan in the context of Islam in Indonesia. These sources include performance records, religious records, and relevant historical literature. In addition, musical analysis is used to understand the musical structure of Javanese gamelan and changes in musical composition and style over time. The results of this study indicate that Javanese gamelan has experienced strong development in the context of Islamic culture in Indonesia. The role of Islam in the development of Javanese gamelan is seen in the influence of Islamic texts on the gamelan repertoire, the use of melodies and themes that reflect Islamic values, and changes in musical styles that are more related to religious practices. This research also highlights efforts to preserve and develop Javanese gamelan as an Islamic cultural heritage. Various communities, institutions and individuals have contributed to maintaining and reviving the Javanese gamelan tradition with Islamic influences.